Focus on seed cells: stem cells in 3D bioprinting of corneal grafts - Xie, Zi-jun; Yuan, Bo-wei; Chi, Miao-miao; Hong, Jing (Frontiers in Bioengineering and Biotechnology, 2024)
Corneal opacity is one of the leading causes of severe vision impairment. Corneal transplantation is the dominant therapy for irreversible corneal blindness. However, there is a worldwide shortage of donor grafts and consequently an urgent demand for alternatives. Three-dimensional (3D) bioprinting is an innovative additive manufacturing technology for high-resolution distribution of bioink to construct human tissues. The technology has shown great promise in the field of bone, cartilage and skin tissue construction. 3D bioprinting allows precise structural construction and functional cell printing, which makes it possible to print personalized full-thickness or lamellar corneal layers. Seed cells play an important role in producing corneal biological functions. And stem cells are potential seed cells for corneal tissue construction. In this review, the basic anatomy and physiology of the natural human cornea and the grafts for keratoplasties are introduced. Then, the applications of 3D bioprinting techniques and bioinks for corneal tissue construction and their interaction with seed cells are reviewed, and both the application and promising future of stem cells in corneal tissue engineering is discussed. Finally, the development trends requirements and challenges of using stem cells as seed cells in corneal graft construction are summarized, and future development directions are suggested.